Internet-offline solution: detail description and benchmarking - Onno W. Purbo (Universitas Ahmad Dahlan, 2020)
In this paper, for the first time, the detail of the Internet-Offline solution for rural/village schools is described, and its benchmarking is reported. For providing offline knowledge access, four (4) different systems have examined. An affordable, the RaspberryPi3 server found to be able to provide web as well as file sharing service for up to 20 clients at 100Mbps throughput. UnixBench shows that the RaspberryPi3 about 25% performance of a four-core i5 system. Using consumer grade power banks at 10000-20000mAh, the RaspberryPi3 server may provide a 6+ hour operation. With reliable electrical power, a mini PC provides a more reliable alternative at an order of magnitude increase in cost. For more than 100 users, one may use i5 or higher engines to keep the price-performance ratio low. Besides, in the Internet-Offline system, teachers no longer have to worry about bullies, hoax, or pornographic contents.